Parental sexual health development support for emerging adolescents in western upstate New York: a qualitative interpretive description study - Natalie M. Leblanc; Sadandaula R. Muheriwa-Matemba; Aaliyah Gray; Osman Wumpini Shamrock; Joyonna Gamble-George; Mary Antwi; Danielle C. Alcena-Stiner; Dalmacio Dennis Flores (Frontiers in Public Health, 2026)
Parents and caregivers are critical in supporting emerging adolescents as they begin developing the foundations of sexual health and wellbeing. This study aimed to explore how parents and caregivers support sexual health development among emerging adolescents aged 10–14 years in Monroe County, New York. A qualitative interpretive description and conventional content analysis approach guided data collection and analysis. Purposive maximum variation and snowball sampling resulted in 20 participants being recruited and engaged in semi-structured in-depth interviews. Parents described sexual health development support as embedded within broader efforts to cultivate self-actualization, autonomy, emotional regulation, bodily awareness, hygiene, consent, and healthy relationships. Four themes characterized parental experiences: parental characterization of their influence on their child's personhood; parental support toward self-actualization; parental approaches toward sexual health development; and perceived threats to sexual health development. Parents reported using anticipatory guidance, open communication, boundary setting, and quality time to prepare their children for emerging social and emotional changes. Their approaches were shaped by their own childhood experiences, including trauma, neglect, cultural values, and prior gaps in sexual health communication. Parents also identified social media, peer influence, structural inequities, and community conditions as threats to healthy sexual development. Findings suggest that sexual health promotion for emerging adolescents should recognize parents as central supports motivated by trauma aversion and enacted through anticipatory guidance shaped by lived experiences, cultural values, and new threats such as social media. Findings conceptualize the parental role in sexual health development as part of whole-person self-actualization. Insights inform the design of trauma-informed, culturally responsive interventions.